Application of optical basicity to viscosity of high alumina blast furnace slags - Ghosh D.; Krishnamurthy V.A.; Sankaranarayanan S.R. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2010)
The composition and properties of blast furnace slags greatly affect the furnace productivity and the quality of hot metal produced. Viscosity is an important physical property of slags, strongly influenced by the chemical composition, structure and the temperature. Experimental measurement of slag viscosity requires high temperature equipment and is time consuming. Therefore, chemical parameters are used to identify trends in viscosity as function of chemical composition. Limited information is available for High Alumina Blast Furnace Slags, since much of the open literature deals with Low Alumina Slags, with alumina content less than 15 weight percentage. High Alumina slags (alumina content in the range of 15% to 30%) are predominantly encountered in Indian Blast Furnaces. It appears that these slags have higher viscosity and lower sulphide capacity than the low alumina slags. The effect of chemical composition / ionic structure on viscosity has been interpreted in this work, using the chemical parameter of optical basicity. Data reported in the literature have been used, along with the values of liquidus temperature, for high alumina slags. Three slag systems, i.e., CaO-Al2O3-SiO2, CaO-Al2O3-SiO2-MgO and CaO-Al2O3-SiO2-MgO-TiO2 have been considered in this work. The trends observed are discussed in the paper.